A Comparative Analysis of the Evolution of Public Space in the Ports of Hormozgan City under Economic and Cultural Paradigm Shifts (A Case Study: Laft, Kong, and Hormoz) - Seyedeh Hosna Hosseini Nasab (منظر)
Public spaces within cities play a crucial role as significant reflections of their identity and social history, characterized by unique features encompassing natural, geographical, economic dynamics, and cultural traditions. The economies of cities and ports in Hormozgan province, historically central to regional fishing and commerce, grapple with challenges related to sustainable development, including the deterioration of historical contexts, rapid population growth, restricted resource access, and environmental degradation. In this context, public spaces, integral focal points in the spatial structure of cities, have undergone changes and faced challenges indicative of these conflicts. The influence of the development-oriented economic and cultural shift shapes the characteristic features of public space, determining its form and functionality. This shift, in turn, either strengthens or weakens the emerging spaces under this role. This study aims to explore the impact of these economic and cultural changes on public spaces, shedding light on the forces that shape their development. The objective of this study is to assess the current state of public spaces and their contribution to sustainable development. The goal is to comprehend the underlying factors influencing the formation of these spaces within the spatial organization of the studied cities and ports, aiming to enhance their development processes. This research employed qualitative methods, relying on field observations, documentary and library studies, and an analytical approach to describe the phenomenon. Through a comparative analysis of the three examined samples, a consistent pattern emerges in the repositioning of public spaces within the spatial organization of the city. The primary catalyst for this shift lies in the creation of economic attractions driven by a rapid increase in tourism. Historically, fishing and shipping dominated the coastal cities’ economy, shaping their structures. However, the current surge in the tourism economy, accompanied by lifestyle changes and increased capital attraction, has not only altered programmatic and financial dynamics but has also impacted the spatial organization of cities. This ongoing transformation, coupled with shifts in the region’s economic structure, has resulted in fundamental changes to the cityscape, rooted in the dominance of the development discourse and native traditions. Consequently, the city’s landscape and landmarks have undergone significant transformations.